Nanotechnology-driven nanoemulsion gel for enhanced transdermal delivery of Sophora alopecuroides L. empyreumatic oil: formulation optimization, and anti-biofilm efficacy - Cheng, Xiuli; Zhou, Xiangyu; Wang, Wenping; Chen, Jing; Cao, Yikun; Wen, Jia; Hu, Jin (Frontiers in Bioengineering and Biotechnology, 2025)
Sophora alopecuroides L. empyreumatic oil (SoA oil) exhibits therapeutic potential for psoriasis and eczema but suffers from poor skin permeability and formulation challenges. To overcome these limitations, a nanoemulsion (NE) gel was developed. The NE was optimized using pseudo-ternary phase diagrams and characterized for droplet size, polydispersity index (PDI), zeta potential, and rheological properties. Skin permeability and retention were assessed in vitro using Franz diffusion cells, with oxymatrine quantified by HPLC. In vivo skin irritation was tested on rabbit dorsal skin, and anti-biofilm activity was evaluated against Staphylococcus aureus (S. aureus) and methicillin-resistant S. aureus (MRSA). A final concentration of 5% SoA oil in the NE formulation was used for subsequent studies. The optimized SoA oil NE (the NE) had a mean droplet size of 53.27 nm, PDI of 0.236, and zeta potential of −38.13 mV. Adding 2% carbomer 940 (CP940) to the gel enhanced viscoelasticity. The NE showed superior skin permeability and higher cutaneous retention of oxymatrine. SoA oil caused moderate irritation to the skin of rabbits, while the other two formulations did not. The NE demonstrated enhanced biofilm inhibition against S. aureus at 0.09766 mg/mL, with an 8.9% rate surpassing SoA oil (2.0%) and SoA oil NE gel (the gel, 4.0%). At 12.50 mg/mL, the NE and the gel achieved slightly higher inhibition rates (81.7% and 82.1%, respectively) than SoA oil (78.3%). Notably, the NE showed significantly greater anti-biofilm effects against MRSA within the concentration range from 0.09766 to 3.12 mg/mL (P < 0.001). In mature biofilm clearance against S. aureus, the NE demonstrated a clearance rate of 4.9% at 0.09766 mg/mL, while SoA oil and the NE gel achieved clearance rates of 2.3% and 0.8%, respectively. At a higher concentration of 12.50 mg/mL, the clearance rate for the NE increased to 38.1%, significantly outperforming SoA oil (29.1%) and the NE gel (36.4%). Against MRSA, the NE and the gel displayed significantly improved clearance at 12.50 mg/mL (42.7% and 43.9%, respectively) compared to SoA oil (31.9%) (P < 0.0001). These findings highlight the potential of nanotechnology-driven delivery systems to improve the clinical application of herbal extracts for treating biofilm-associated dermatological infections.